De novo Assembly and Characterization of the Transcriptome of Broomcorn Millet (Panicum miliaceum L.) for Gene Discovery and Marker Development - Yue, Hong; Wang, Le; Liu, Hui; Yue, Wenjie; Du, Xianghong; Song, Weining; Nie, Xiaojun (Frontiers in Plant Science, 2016)
Broomcorn millet (Panicum miliaceum L.) is one of the world’s oldest cultivated cereals, which is well-adapted to extreme environments such as drought, heat, and salinity with an efficient C4 carbon fixation. Discovery and identification of genes involved in these processes will provide valuable information to improve the crop for meeting the challenge of global climate change. However, the lack of genetic resources and genomic information make gene discovery and molecular mechanism studies very difficult. Here, we sequenced and assembled the transcriptome of broomcorn millet using Illumina sequencing technology. After sequencing, a total of 45,406,730 and 51,160,820 clean paired-end reads were obtained for two genotypes Yumi No. 2 and Yumi No. 3. These reads were mixed and then assembled into 113,643 unigenes, with the length ranging from 351 to 15,691 bp, of which 62,543 contings could be assigned to 315 gene ontology (GO) categories. Cluster of orthologous groups and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses assigned could map 15,514 unigenes into 202 KEGG pathways and 51,020 unigenes to 25 COG categories, respectively. Furthermore, 35,216 simple sequence repeats (SSRs) were identified in 27,055 unigene sequences, of which trinucleotides were the most abundant repeat unit, accounting for 66.72% of SSRs. In addition, 292 differentially expressed genes were identified between the two genotypes, which were significantly enriched in 88 GO terms and 12 KEGG pathways. Finally, the expression patterns of four selected transcripts were validated through quantitative reverse transcription polymerase chain reaction analysis. Our study for the first time sequenced and assembled the transcriptome of broomcorn millet, which not only provided a rich sequence resource for gene discovery and marker development in this important crop, but will also facilitate the further investigation of the molecular mechanism of its favored agronomic traits and beyond.